Optimalisasi Penguatan Profil Pelajar Pancasila (P5) Melalui Gelar Karya sebagai Penerapan Nilai Pancasila di SMK NU 1 Sukodadi - Winda Safitri; Frischa Vera Yunida; Yanuangga Galahartlambang; Agustinus Salukh; Tri Winarsih (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
The Pancasila Student Profile Strengthening Project (P5) aims to develop students who possess strong character and skills that are relevant to the demands of the times, particularly in facing global challenges and technological advancements. One of the implementations of P5 at SMK NU 1 Sukodadi is the Gelar Karya activity, which serves as a platform for students to showcase their creativity and apply the values of Pancasila in real life. The theme of this activity is "Build a Healthy Body, Mind, and Sustainable Lifestyle," aimed at raising awareness of the importance of physical and mental health, as well as adopting environmentally friendly practices that support sustainability. The method used in this activity is a project-based learning approach, where students are given the opportunity to learn through direct experience. This allows them to understand and apply the theories they have learned in real-world practices. Additionally, the activity emphasizes collaboration between students and teachers, creating a supportive learning environment and strengthening the relationship between learners and educators. By utilizing experiential learning, students are directly involved in the learning process, which facilitates a deeper understanding. The results of this community service project show that the Gelar Karya activity successfully increased students' awareness of the importance of healthy lifestyles and sustainable environmental management. Students not only gained theoretical knowledge but also practical skills that they can apply in their daily lives. Furthermore, the activity strengthened students' character and supported the values of the Pancasila Student Profile. These findings can serve as a model for other schools to optimize the sustainable implementation of P5, providing a positive impact on shaping students' character and skills for a better future.